Use of Theses and Reports in Master's Degree Programs. - Anderson, Wilton T.; Usry, Milton F. (The Accounting Review, 1970)
The article discusses the results of a survey that examined the factors affecting theses and reports in master's degree programs of business schools. The role of graduate education for business is becoming increasingly important. Many educators believe that research and writing experience, from thesis or report assignments, can be an especially valuable part of the educational process in graduate work. In both AACSB and other schools, the Master of Business Administration (MBA) with no specified major was the most prevalent. However, when the MBA with a major or option in accounting, hereinafter referred to as "MBA-accounting option," is combined with the MS or MA in Accounting category, these two accounting concentration degrees exceeded the MBA-no major class. In two-thirds of the schools surveyed a student can engage in in-depth study in the field of accounting at the graduate level. In many of the schools two or more master's degrees were offered. The status of the report in masters programs having accounting concentrations suggests a greater degree of research orientation than in the MBA-no major programs.